Otoritas Teks dan Dinamika Hukum Keluarga:: Reinterpretasi Mu‘āsyarah bi al-Ma‘rūf dalam Tafsir Aḥkām Surah al-Nisā’:19 - Al Amin, Habibi (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2026)
This article examines the interpretative authority regarding Sūrah al-Nisā':19, focusing on the principle of mu'āsyarah bi al-ma'rūf and its relevance to the reform of contemporary Islamic family law. This research stems from the issue that this verse has long served as the normative basis for marital relations, yet its interpretation remains a subject of debate between a textual-normative reading and a contextual-ijtihadi reading. Using a qualitative literature review method through a thematic-comparative exegetical approach and critical hermeneutic analysis, this article examines classical exegesis, modern exegesis, and contemporary literature on maqāṣid al-sharī'ah, the authority of exegesis, and gender justice. The findings indicate that mu'āsyarah bi al-ma'rūf cannot be reduced to mere individual moral ethics, but rather constitutes a legal-ethical principle that demands realisation through justice, the public interest, respect for human dignity, and the protection of vulnerable family members. This article concludes that the authority of the text remains important, but its application requires a dialogical ijtihad that is responsive to the contemporary social context.